2016
DOI: 10.3855/jidc.6800
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect of probiotics on bacterial species from dental plaque

Abstract: Introduction: The antimicrobial role of probiotic Lactobacillus casei subspecies casei DG (L. casei DG) and of the mix culture of probiotic Lactobacillus acidophilus LA-5 and Bifidobacterium BB-12 was tested on species of Staphylococcus, Streptococcus, Pasteurella, and Neisseria genera from supragingival sites from dogs with dental disease of different breed, age, sex, weight, and diet. The research was conducted on these four genera because of their importance in zoonotic infections after dog bites. Methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…This was confirmed in the present study, which verified the presence of the genera Staphylococcus, Streptococcus, Actinomyces and Neisseria (as shown in Figure 1). As expected, the genera Porphyromonas, Fusobacterium and Veillonella, found in other works [19,22,23,24] were not isolated as result of the methodology applied and the nutritional and strict anaerobic needs of these bacteria.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This was confirmed in the present study, which verified the presence of the genera Staphylococcus, Streptococcus, Actinomyces and Neisseria (as shown in Figure 1). As expected, the genera Porphyromonas, Fusobacterium and Veillonella, found in other works [19,22,23,24] were not isolated as result of the methodology applied and the nutritional and strict anaerobic needs of these bacteria.…”
Section: Discussionsupporting
confidence: 82%
“…The sequence analyses and literature review indicated that 59/179 (33%) of the bacteria isolated from dogs in this study are not normally found in human oral cavities [26,27]. Only 5/15 (33.3%) of the identified groups (14 genera plus Bisgaard taxon 16), namely Actinomyces, Neisseria, Haemophilus, Streptococcus and Lactobacillus, are considered members of human dental supragingival plaque [22,23].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Zambori et al (64) have highlighted the antimicrobial potential of probiotics in vitro. More specifically, it was demonstrated that Lactobacillus casei, subsp.…”
Section: Emerging Methods For the Treatment Of Biofilmsmentioning
confidence: 99%